The future leader : 9 skills and mindsets to succeed in the next decade - Morgan, Jacob, 1983- (John Wiley & Sons, Inc., 2020)
"A research based book to help organizations understand what they need to do now in order to build the leader of the future. There are many great leadership books which deal with the present day, but organizations around the world are changing quickly that we don't need to know how to create great leaders now, we need to know how to plan for the future. As Wayne Gretzky says, "Skate to where the puck is going, not where it has been." This book is about where the puck is going and will be based on as series of one-on-one executive interviews, surveys, and behavioral data collected through third parties to determine what skills leaders of the future are going to need to possess and what organizations need to do today to make sure they are instilling those skills for future or current leaders. This is a huge topic of concern for organizations that are worried about how technology, changing demographics, shorter tenure, gig work, changing power dynamics, etc are going to impact the way we work and the skills required for leading in that new world of work. During all the talks I give today, the question always come up, "we get how things are changing now and we understand what we need to be doing, but how do we plan for the future?" This book will help organizations skate to where the puck is going, when it comes to leadership. It will help them understand the skills that leaders will need to possess in the coming years and will help them implement strategies to make that leaders acquire those skills"--